2012
DOI: 10.1080/00028487.2012.676590
|View full text |Cite
|
Sign up to set email alerts
|

Age and Growth of Atlantic Sturgeon in the James River, Virginia, 1997–2011

Abstract: Historically the Chesapeake Bay supported a large population of Atlantic sturgeon Acipenser oxyrinchus, but loss of suitable spawning habitat and overfishing coincided with dramatic in‐system declines throughout the 20th century. Atlantic sturgeon harvest moratoriums were implemented in 1974 for Virginia waters and were expanded coastwide in 1998. In 1997, researchers became aware that commercial fishers in the James River, a tributary of the Chesapeake Bay, were catching juvenile and subadult Atlantic sturgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
15
2
Order By: Relevance
“…Age estimation is challenging in older adult sturgeon, because of the close spacing of annuli near the edge of the pectoral fin spine (Nathan, et al, 2015), so the higher agreement may be attributable to our specimens being juveniles. In the present study, both sturgeon species presented higher CV between readers than the 1.8% in juvenile lake sturgeon Acipenser fulvescens (Balazik, McIninch, Garman, & Latour, 2012). The CV of Amur sturgeon was lower than the reported 13.6% in juvenile pallid sturgeon Scaphirhynchus albus, while the CV of kaluga was lower than that reported for juvenile pallid sturgeon S. albus (Koch et al, 2011).…”
Section: Discussioncontrasting
confidence: 70%
“…Age estimation is challenging in older adult sturgeon, because of the close spacing of annuli near the edge of the pectoral fin spine (Nathan, et al, 2015), so the higher agreement may be attributable to our specimens being juveniles. In the present study, both sturgeon species presented higher CV between readers than the 1.8% in juvenile lake sturgeon Acipenser fulvescens (Balazik, McIninch, Garman, & Latour, 2012). The CV of Amur sturgeon was lower than the reported 13.6% in juvenile pallid sturgeon Scaphirhynchus albus, while the CV of kaluga was lower than that reported for juvenile pallid sturgeon S. albus (Koch et al, 2011).…”
Section: Discussioncontrasting
confidence: 70%
“…Balazik et al. () found that out of five candidate models, the Gompertz model was the second‐best model for growth estimation of Atlantic Sturgeon A. oxyrinchus oxyrinchus in the James River, Virginia. Additionally, Woodland () found that the Gompertz model seemed to fit length‐at‐age data for Hudson River Shortnose Sturgeon A. brevirostrum , but an information‐theoretic approach was not applied in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Balazik et al. () selected the double VBGF as the best model among five candidate models for Atlantic Sturgeon growth in the James River based on length‐at‐age data. The inclusion of that model as well as data for older individuals of Gulf Sturgeon and data from different drainages will improve the ability to identify the most appropriate growth model for Gulf Sturgeon across the GOM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations